Analisis Dukungan Keluarga Terhadap Perilaku Ibu Dalam Perawatan Kehamilan Di BPM Restu Ibu Sragen - Widy Nurwiandani; Ari Andriyani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Background: Maternal death in the reproductive process is a worrying tragedy, because thepresence of a mother is the main milestone for achieving a prosperous family and the death of amother is a disaster for her family2. For this reason, the mother's attitude in preventing pregnancycomplications or to reduce pregnancy complications early is to carry out routine checks according tothe recommendations of health workers (Doctors, Midwives). So that mothers, husbands and familiescan find out as soon as possible how to prevent pregnancy complications and if there are problemsthat arise in pregnancy3. Mortality and morbidity in pregnant women is a major problem in developingcountries. In poor countries around 25-50%. The death of fertile women is caused by things related topregnancy. Death during childbirth is usually a major factor in the mortality of young women at theirpeak of productivity. In 1996 WHO (Word Health Organization) estimated that more than 585,000mothers per year died during pregnancy or childbirth, actually more than 50% of deaths in 2developing countries. The deaths of pregnant women in Indonesia are bleeding, infection andeclampsia, besides that, deaths due to abortion and prolonged labor are also included. About 50% ofmaternal deaths are caused by diseases that worsen due to pregnancy, such as heart disease and chronic infections. The results of a preliminary study of 10 pregnant women regarding family supportfor prenatal care, it turns out that there are still 80% (8 people) pregnant women get very goodsupport from their husbands and families, while 20% (2 people) pregnant women get a lot of supportfrom their husbands. as well as family.Objective : To find out family support for the behavior of pregnant women in pregnancy care at BPMRestu Ibu Sragen.Methods : This research was conducted at BPM Restu Ibu Sragen in August 2021. The researchdesign used univariate correlation with this research design using cross sectional.Results : By using the Chi-Square formula and the contingency coefficient, it was found that 53.3% ofpregnant women received support from their families and 60% of pregnant women did not regularlyperform prenatal care. The results of the cross tabulation between family support and maternalbehavior in pregnancy care showed that 40% of pregnant women who did not receive family supportbehaved irregularly in pregnancy care, with the results of x2 count = 7.22 and x2 table = 3.84 wherex2 count > x2 table with a significant level of 0.05.Conclusion: There is a relationship between family support and maternal behavior in pregnancy careat BPM Restu Ibu Sragen.Keywords: Family Support, Behavior of Pregnant Women